The Role of Agency Cost as a Mediator in the Effect of Capital Structure on Company Financial Performance - Hutapea, Agnes Agataha Br; Sulistyowati, Erna (Indonesian Journal of Sustainability Policy and Technology, 2024)
The objective of this study is to examine the impact of capital structure on agency cost, the impact of agency cost on corporate financial performance, and to assess the indirect impact of capital structure on corporate financial performance through agency cost acting as an intervening variable. The subjects of this study are the cement sub-sector companies publicly traded on the Indonesia Stock Exchange (IDX) during the years 2014 and 2018. This study employed a saturated sampling technique, specifically census sampling, which resulted in a sample of 30 enterprises. In this study, the capital structure is measured using the debt-equity ratio (DER), while the company's financial performance is measured using return on equity (ROE). This research employed SmartPLS 3.0 software for testing purposes. The findings of this study suggest that the capital structure, represented by the debt-to-equity ratio (DER), has a detrimental impact on agency costs. Additionally, agency cost negatively influences corporate financial performance, as measured by return on equity (ROE). However, the study did not find any indirect effect of capital structure on financial performance through agency cost as an intervening variable.